Environmental Perception how elaboration instrument in the strategies of the Environmental Education - Nunes, Daniela Marques; Marangoni, Vinicius (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The study aimed to record the Environmental Perception of residents in an urban center of the metropolitan area of Porto Alegre, RS, in order to support environmental education strategies in the management of solid waste. The survey was conducted through semi-structured with questions regarding the disposal of household waste by residents questionnaires. The results indicated that 60 % of residents separated the dry organic waste, yet 38 % did not have the habit of discarding it clean. The largest disseminators agents information regarding selective collection in the city were the vehicles of mass communication and the Formal Education. The results showed the way forward for the development of strategies for environmental education to local problems facing the region.